Assessment Of Vaginal Infections In Pregnant Women (Journal of Pharmaceutical Negative Results, 2022)
Background: Vaginitis is inflammation of the vagina. Vulvovaginitis, is an inflammation of the vagina and vulva. Infection can resultin discharge, itching and pain. The present study was conducted to assess vaginal infections in pregnant women.Materials & Methods: 76 pregnant women reporting to Obstetric & Gynaecology department for vaginal infection. A detailed obstetricexamination was carried out as well. Per speculum examination was carried out and the vaginal mucosa was inspected for the presenceof erythema, lesions, and discharge. Vaginal and cervical swabs samples were obtained and sent to microbiology laboratory.Results: There were 10 in first trimester, 26 in second and 40 in third trimester. The difference was significant (P< 0.05). Clue cells inwet mount was positive in 8 and negative in 68, Nugent’s score >7 was positive in 12 and negative in 64. Amsel’s criteria was positivein 14 and negative in 62. The difference was significant (P< 0.05). Gram’s stain was positive in 5 and negative in 71 and culture waspositive in 11 and negative in 65. The difference was significant (P< 0.05).Conclusion: Bacterial vaginosis was seen in 14 and candidiasis in 11 cases. Diagnosis of vaginal infections was done using both clinicaland microbiological methods.